Jesus' Prophethood and Islam: Insights from the Risale‐i Nur. (September 2014) - Largen, Kristin Johnston
Abstract While Jesus' prophethood is an indisputable component of his identity in the Christian tradition, it has been marginalized for centuries in favor of his identity as savior. In this article, I argue that an engagement with an understanding of Jesus' prophethood in Islam, particularly as explicated by the Turkish thinker Bediüzzaman Said Nursi, can help Christians recover a more robust interpretation of Jesus as prophet that has a positive impact on a Christian articulation of the church and of discipleship today.